A retrospective analysis of magnetic resonance cholangiopancreatography investigating gallstones in a contemporary surgical setting. Issue 9 (29th June 2022) - Robinson, Christian; Turner, Robin M.; Potter, Jon
Abstract: Backgrounds: The New Zealand Public Health System operates in a resource limited environment. Pre‐operative investigation of choledocholithiasis (CDL) is variable. Protocol driven practice has improved patient outcomes and cost‐effectiveness. The aim is to explore risk stratification for CDL and specific thresholds for accessing magnetic resonance cholangiopancreatography (MRCP) in this contemporary setting. Methods: All adult (16+ years) acute inpatient MRCP requests for gallstone work‐up between 1 Jan 2018 and 2031 Dec 2019 at Dunedin Hospital were included. Patients with characteristics not in fitting with an acute symptomatic examination were excluded. Receiver operating characteristic curves were estimated for bilirubin versus MRCP positive by the presence/absence of dilated ducts, indication and American Society of Gastrointestinal Endoscopy (ASGE) risk grouping. Results: A 106 patients were included. Mean bilirubin at presentation and time of MRCP, 47 versus 28 μmol/L, respectively. MRCP confirmed CDL in 39 (37%) patients. 38 (97%) had biochemical changes with choledocholithiasis. 21 (40%) with CBD dilation had ductal stones versus 18 (34%) with normal ducts. ASGE risk stratification showed 36 (34%), 66 (62%) and 4 (4%) were high, intermediate and low risk, respectively. Of these groups 44%, 35% and 0% had CBD stones on MRCP, respectively. Combination thresholds involving duct size and bilirubin can yield negative predictive values >90%, substantially reducing MRCP load. Conclusions: MRCP requests can be triaged to maximize stones detected without overly increasing the rate of missed duct stones whilst protecting the limited MRI and ERCP resources. International thresholds and risk stratification alone may not be applicable in our resource limited environment.